Patient and Surrogate Views of Community Consultation for Emergency Research. (23rd October 2017) - Fehr, Alexandra E.; Scicluna, Victoria M.; Pentz, Rebecca D.; Haggins, Adrianne N.; Dickert, Neal W.
Abstract: Objective: Pretrial community consultation (CC) is required for emergency research conducted under an exception from informed consent (EFIC) in the United States. CC remains controversial and challenging, and minimal data exist regarding the views of individuals enrolled in EFIC trials on this process. It is important to know whether participants perceive CC to be meaningful and, if so, whom they believe should be consulted. Methods: We conducted a secondary analysis of data from two studies interviewing patients and surrogates of two recent EFIC trials (PEER‐RAMPART and PEER‐ProTECT). These interviews included similar open‐ and closed‐ended questions regarding participants' views of the importance of CC, the rationale for their responses, and their views regarding which populations should be included in consultation efforts. A template analytic strategy was used for qualitative analysis of textual data, and descriptive statistics were tabulated to characterize demographic data and instances of major themes. Results: Ninety percent of participants perceived CC to be valuable. Participants' reasons for finding CC valuable clustered in two categories: 1) as a method of informing the public about the trial to be conducted and 2) as a way of obtaining input and feedback from the community. Participants cited the medical community (43%) and individuals with a connection to the study condition (41%) as the most important groups to involve in consultation efforts; only 5% suggested consulting the general public in the area where the research will be conducted. Conclusion: Participants in EFIC trials and their decision makers generally valued CC as a method of informing and seeking input from the community. Participants felt that the most appropriate groups to consult were the medical community and individuals with connections to the condition under study. Consultation efforts focused on these two groups, rather than the general public, may be more efficient and more meaningful to individuals involved in EFIC trials. These findings also reinforce the importance of the distinction between public disclosure and CC.